Holistic management : - Christopher, William F. (Wiley-Interscience, 2007)
This book presents two recently developed knowledge areas that can significantly improve the management and the performance of business enterprise: System Science and Cybernetics and Key Performance Areas. Included in this book are advanced (and evolving) methods and technologies for planning and budgeting, creating and keeping customers, quality and productivity, innovation, improving organization capability, sustainability in the company's social and ecological environments, and profitability-all integrated with this new viable systems model and system thinking